2022
DOI: 10.3389/fphar.2022.966279
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 neuroinflammatory factors may be involved in atopic dermatitis mental disorders: an animal study

Abstract: Background: Numerous clinical studies have shown that atopic dermatitis (AD) is often associated with mental disorders. This could contribute to the overall burden of atopic dermatitis. However, the underlying mechanism of mental health symptoms in AD has not been fully elucidated.Methods: An AD mouse was induced by 2,4-dinitrofluorobenzene (DNFB), which was repeatedly applied to the back skin of the BALB/C mice to establish an atopic dermatitis mental disorder model. The role of neuroinflammation in the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…As a result of AD, IL-5 synthesis by human Th cells is dependent on MAP kinase activity, which promotes an intense inflammatory state in AD (Mori et al, 1999). In patients with AD, neuroinflammatory response related to AD mental disorders closely (Yuan et al, 2022). Regulation of leukocyte migration was closely related to adhesion molecules on endothelial cells, and which reflected the extent of systemic inflammation, such as AD (Yamashita et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of AD, IL-5 synthesis by human Th cells is dependent on MAP kinase activity, which promotes an intense inflammatory state in AD (Mori et al, 1999). In patients with AD, neuroinflammatory response related to AD mental disorders closely (Yuan et al, 2022). Regulation of leukocyte migration was closely related to adhesion molecules on endothelial cells, and which reflected the extent of systemic inflammation, such as AD (Yamashita et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a hypothetical “skin-brain axis” has been proposed in which dermal inflammation would trigger mental disorders. Supporting this conjecture, experimental induction of dermatitis in mice increased anxiety- and depressive-like behaviors, along with elevated serum corticosterone levels [ 81 ]. More convincingly, in clinical trials, anti-IL17A [ 82 ] and anti-IL4R [ 83 ] antibodies which target inflammatory signaling in the skin, reduced psoriatic lesions and atopic dermatitis, respectively, as they simultaneously mitigated anxiety and depression.…”
Section: Hallmark 1: Integrity Of Barriersmentioning
confidence: 98%
“…Studies showed that the expression of inflammasome NLR Family Pyrin Domain Containing 3 (NLRP3) and absent in melanoma-2 (AIM2) was increased in AD and was related to epidermal inflammation [ 11 , 12 ]. Moreover, NLRP3, caspase-1, and IL-1B, involved in the pyroptosis canonical pathway, might be related to mental disorders of AD [ 13 ]. These findings indicated that PRGs may act as a pivotal part of AD and identifying more comprehensive potential PRBMs can provide a novel perspective on the diagnosis and treatment of AD.…”
Section: Introductionmentioning
confidence: 99%